Anatomical Alterations in Plant Tissues Induced by Plant-Parasitic Nematodes - Palomares-Rius, Juan E.; Escobar, Carolina; Cabrera, Javier; Vovlas, Alessio; Castillo, Pablo (Frontiers in Plant Science, 2017)
Plant-parasitic nematodes (PPNs) interact with plants in different ways, for example, through subtle feeding behavior, migrating destructively through infected tissues, or acting as virus-vectors for nepoviruses. They are all obligate biotrophic parasites as they derive their nutrients from living cells which they modify using pharyngeal gland secretions prior to food ingestion. Some of them can also shield themselves against plant defenses to sustain a relatively long lasting interaction while feeding. This paper is centered on cell types or organs that are newly induced in plants during PPN parasitism, including recent approaches to their study based on molecular biology combined with cell biology-histopathology. This issue has already been reviewed extensively for major PPNs (i.e., root-knot or cyst nematodes), but not for other genera (viz. Nacobbus aberrans, Rotylenchulus spp.). PPNs have evolved with plants and this co-evolution process has allowed the induction of new types of plant cells necessary for their parasitism. There are four basic types of feeding cells: i) non-hypertrophied nurse cells; ii) single giant cells; iii) syncytia; and iv) coenocytes. Variations in the structure of these cells within each group are also present between some genera depending on the nematode species viz. Meloidogyne or Rotylenchulus. This variability of feeding sites may be related in some way to PPN life style (migratory ectoparasites, sedentary ectoparasites, migratory ecto-endoparasites, migratory endoparasites, or sedentary endoparasites). Apart from their co-evolution with plants, the response of plant cells and roots are closely related to feeding behavior, the anatomy of the nematode (mainly stylet size, which could reach different types of cells in the plant), and the secretory fluids produced in the pharyngeal glands. These secretory fluids are injected through the stylet into perforated cells where they modify plant cytoplasm prior to food removal. Some species do not produce specialized feeding sites (viz. Ditylenchus, Subanguina), but may develop a specialized modification of the root system (e.g., unspecialized root galls or a profusion of roots). This review introduces new data on cell types and plant organs stimulated by PPNs using sources varying from traditional histopathology to new holistic methodologies.